THE EXPERIENCE OF THE USING PICTURE THERAPY AS A METHOD OF OVERCOMING THE AGRESSION OF PRIMARY SCHOOL CHILDREN - Барановська, Лілія Володимирівна; Главінська, Еліна Сергіївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article is devoted the experience of the using imaging therapy as an art-therapeutic method of diagnosis and psychocorrection of aggressiveness of children of primary school age. Theoretical analysis of the specificity of using picture therapy methods with the application of different types of fine arts in the work with the emotional sphere, in particular the problem of aggressive behavior as a result of the unmet needs of the child is carried out. The views of psychologists of art-therapists on the question of the expediency of using image therapy in work with children are analyzed. The issues of causes and types of aggression of children of primary school age are considered, possible negative consequences of the aggressive behavior as well as the features and advantages of using picture therapy in work overcoming the aggression and aggressive behavior of children of primary school age. A decrease in the level of aggressiveness of children of primary school age due to the implementation of a psychocorrectional program using the methods of imaging therapy was experimentally found. Practical recommendations are given to psychologists, educators, parents and pupils to reduce the level of aggression by means of picture therapy. Picture therapy is one of the types of art therapy, it is a universal method of psychological influence, because it can be used as a method of psychological influence on people of different ages, who have different problems. Drawing activates the brain of the child, because in the process of drawing coordinated both visual and imaginative thinking, and in the process of discussing with the child created drawings – abstract. Image therapy is a progressive method in psychocorrection, psychotherapy and psychological counseling with the use of art, creativity and the development of imagination and creativity. The main purpose and value of such therapy is that it develops the child’s ability to express himself and self-knowledge, thereby harmonizing his mental state. With the help of art, on a symbolic level, you can express and explore a wide variety of feelings and emotions: love, hatred, image, anger, fear, joy, etc.